একাত্তরের রণাঙ্গন, গেরিলাযুদ্ধ ও হেমায়েতবাহিনী - উল্লাহ, মোহাম্মদ সফিক. 1941- (ঢাকা : আহমদ পাবলিশিং হাউস, 2004)
Role of a group of revolutionaries under the leadership of Hemāẏetauddina, b. 1941, in the liberation war of Bangladesh, 1971.
In Bengali; includes passages in English.
Keywords: Hemāẏetauddina, -- 1941- -- Influence; Bangladesh -- History -- Revolution, 1971 -- Personal narratives